Understanding PhD Holders’ First Work Destination - Nathan Gurnet; Bernard Fusulier (Recherches Sociologiques et Anthropologiques)
Due to the saturation of the academic market, the employment of PhD graduates has become an important issue in higher education studies. In this article, we measured to what extent the internalisation of a scientific ethos and previous professional socialisation affect the employment trajectories of recently proclaimed PhDs (academic, non-academic or precarious). To this end, we developed statistical models based on a sample of 268 PhD graduates in French-speaking Belgium. Two main results emerge from the modelling. Firstly, acculturation to the scientific ethos is highly dependent on the norms in force in the respondents’ work environment. Secondly, the internalization of this ethos plays an important role in job destination. PhD graduates who conform more closely to academic norms are less likely to hold non-academic jobs than academic ones. In contrast, we observe no significant effect of ethos between PhD holders who end up in academic or precarious employment. Therefore, respect for scientific norms could be interpreted as a factor that hinders recruitment outside academia.